Bobby Burkholder - Sahl, Ted (photographer):::Creator::::::::::::
Photograph is a portrait of Bobby Burkholder. He is wearing a teeshirt that reads: "The Mens Room" and has his arms crossed over his midsection. Bobby was Mr. Gay San Jose, 1980